Winding down the Chicxulub impact: The transition between impact and normal marine sedimentation near ground zero - Whalen, M.T.; Gulick, S.P.S.; Lowery, C.M.; Bralower, T.J.; Morgan, J.V.; Grice, Kliti; Schaefer, Bettina; Smit, J.; Ormö, J.; Wittmann, A.; Kring, D.A.; Lyons, S.; et al. (ELSEVIER, 2020)
The Chicxulub impact led to the formation of a ~ 200-km wide by ~1-km deep crater on México's Yucatán Peninsula. Over a period of hours after the impact the ocean re-entered and covered the impact basin beneath several hundred meters of water. A suite of impactites were deposited across the crater during crater formation, and by the resurge, tsunami and seiche events that followed. International Ocean Discovery Program/International Continental Scientific Drilling Program Expedition 364 drilled into the peak ring of the Chicxulub crater, and recovered ~130 m of impact deposits and a 75-cm thick, fine-grained, carbonate-rich “Transitional Unit”, above which normal marine sedimentation resumed. Here, we describe the results of analyses of the uppermost impact breccia (suevite) and the Transitional Unit, which suggests a gradual waning of energy recorded by this local K-Pg boundary sequence. The dominant depositional motif in the upper suevite and the Transitional Unit is of rapid sedimentation characterized by graded bedding, local cross bedding, and evidence of oscillatory currents. The lower Transitional Unit records the change from deposition of dominantly sand-sized to mainly silt to clay sized material with impact debris that decreases in both grain size and abundance upward. The middle part of the Transitional Unit is interrupted by a 20 cm thick soft sediment slump overlain by graded and oscillatory current cross-laminated beds. The uppermost Transitional Unit is also soft sediment deformed, contains trace fossils, and an increasing abundance of planktic foraminifer and calcareous nannoplankton survivors. The Transitional Unit, as with similar deposits in other marine target impact craters, records the final phases of impact-related sedimentation prior to resumption of normal marine conditions. Petrographic and stable isotopic analyses of carbon from organic matter provide insight into post-impact processes. δ13Corg values are between terrestrial and marine end members with fluctuations of 1–3‰. Timing of deposition of the Transitional Unit is complicated to ascertain. The repetitive normally graded laminae, both below and above the soft sediment deformed interval, record rapid deposition from currents driven by tsunami and seiches, processes that likely operated for weeks to potentially years post-impact due to subsequent continental margin collapse events. Highly siderophile element-enrichment at the top of the unit is likely from fine-grained ejecta that circulated in the atmosphere for several years prior to settling. The Transitional Unit is thus an exquisite record of the final phases of impact-related sedimentation related to one of the most consequential events in Earth history.